Aligned PCL Fiber Conduits Immobilized with Nerve Growth Factor Gradients Enhance and Direct Sciatic Nerve Regeneration. (13th August 2020) - Zhu, Lei; Jia, Shuaijun; Liu, Tuanjiang; Yan, Liang; Huang, Dageng; Wang, Zhiyuan; Chen, Shi; Zhang, Zhengping; Zeng, Wen; Zhang, Ying; Yang, Hao; Hao, Dingjun
Abstract: Topographical guidance and chemotaxis are crucial factors for peripheral nerve regeneration. This study describes the preparation of highly aligned poly(ε‐caprolactone) (PCL) fiber conduits coated with a concentration gradient of nerve growth factor (NGF) (A/G‐PCL) using a newly designed electrospinning receiving device. The A/G‐PCL conduits are confirmed in vitro to enhance and attract the neurite longitudinal growth of dorsal root ganglion (DRG) neurons toward their high‐concentration gradient side. In vivo, the A/G‐PCL conduits are observed to direct a longitudinal stronger attraction of axons and migration of Schwann cells in 15 mm rat sciatic nerve defects. At 12 weeks, rats transplanted with A/G‐PCL conduits show satisfactory morphological and functional improvements in g‐ratio, total number, and area of myelinated nerve fibers as well as the sciatic function index, compound muscle action potentials, and muscle wet weight ratio as compared to aligned PCL fibers conduits with uniform NGF (A/U‐PCL). The performance of A/G‐PCL is similar to that of autografts. Moreover, mRNA‐seq and RT‐PCR results reveal that Rap1, MAPK, and cell adhesion molecules signaling pathways are closely associated with axon chemotactic response and attraction. Altogether, by combining structural guidance with axon chemotaxis, the NGF‐gradient/aligned PCL fiber conduits represent a promising approach for peripheral nerve defect repair. Abstract : Topographical guidance and chemotaxis are crucial factors for peripheral nerve regeneration. Herein, a new method for fabricating highly aligned poly(ε‐caprolactone) fiber conduits coated with a concentration gradient of NGF is proposed. Moreover, the genes and molecules signaling pathways associated with axon chemotactic response are explored. Finally, a 15 mm rat sciatic nerve defect is functionally bridged by using the new conduit, the biological structure and function performance of the regenerated nerve are similar to those of the nerve autograft.